Acute-lethal toxicity test on juvenile Oreochromis niloticus exposed to Piper betle extract under static exposure - Mustapha, Siti Nurafiqah; John, Akbar; Sheikh, Hassan; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman (Emerald Publishing Limited, 2020)
Purpose This study aims to evaluate the effect of Piper betle leaf extract towards the acute-lethal toxicity, LC50 of red Nile tilapia juveniles (Oreochromis niloticus).